2019
DOI: 10.12968/jowc.2019.28.sup1.s4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis on the healing time and infection rate of diabetic foot ulcers in a referral wound care clinic

Abstract: Objective: Objectives. To determine the prevalence and risk factors for diabetic foot infection (DFI), and to identify factors associated with delayed wound healing of diabetic foot ulcer (DFU). Method: The retrospective study was performed in a referral wound care clinic in Hospital Kuala Lumpur. Data was collected from January 2014 to October 2016 on DFU patients who attended this clinic. Results: Of the 340 patients (216 male and 124 female) DFU patients who attended the clinic (mean age: 58.1±10.8 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The factors that we found to be significantly associated with a longer ulcer duration were infection and toe localization of the ulcer. Infected ulcers have previously been connected to prolonged ulcer healing time [14, 15] and toe localization to shorter healing time compared to the mid and the hind foot [5, 16].…”
Section: Resultsmentioning
confidence: 99%
“…The factors that we found to be significantly associated with a longer ulcer duration were infection and toe localization of the ulcer. Infected ulcers have previously been connected to prolonged ulcer healing time [14, 15] and toe localization to shorter healing time compared to the mid and the hind foot [5, 16].…”
Section: Resultsmentioning
confidence: 99%
“…days. Time greater than that was found in two national studies: 9% in Tavares et al 16 and 14% by Borboletto et al 6 , which may be justified by the clinical conditions on the patients' admission, as well as complications related to the delay in hospitalization 4,[16][17][18] .…”
Section: Resultsmentioning
confidence: 74%
“…After all, DFUs usually take a long time to be cured. Several studies have shown that the mean or median healing time ranged from 2 to 4 months, even for those treated with AMs [32][33][34][35]. Further studies are needed to explore the short-term effects of AMs.…”
Section: Discussionmentioning
confidence: 99%